Improvement of two-phase refrigerant distribution for upward flow of a parallel flow minichannel heat exchanger using insertion devices. (September 2019) - Kim, Nae-Hyun; Kim, Cheol-Hwan; Shah, Yousaf; Li, Wei
Highlights: Insert devices for an improved flow distribution in a 36 parallel flow channel. Perforated tube, perforated tube/perforated plate, orifice/perforated tube, concentric perforated tube. Concentric perforated tube yielded the best flow distribution. The preferred configuration of the concentric perforated tube was dependent on the mass flux. Abstract: In a parallel flow heat exchanger, significant mal-distribution of flow occurs due to phase separation. In this study, various insert devices (perforated tube, perforated tube with perforated plate, orifice and perforated tube, concentric perforated tube) were investigated to obtain an improved flow distribution in a 36 channel parallel flow heat exchanger. The test section was made to closely simulate an actual heat exchanger. Tests were conducted for upward flow for the mass flux from 57 to 241 kg m −2 s −1 and quality from 0.2 to 0.4 using R-410A. Of the investigated insert devices, concentric perforated tube yielded the best flow distribution. Insertion of the concentric perforated tube reduced the thermal degradation from 61% to 14%. Furthermore, the preferred number of holes of the concentric perforated tube was dependent on the mass flux. At a low mass flux, an insert having small number of holes was preferred, whereas the reverse was true at a high mass flux. At a low mass flux, the effect of inlet vapor quality on flow distribution was significant. At a high mass flux, however, the effect of vapor quality on flow distribution was minimal. Possible explanations on the flow distribution behavior were provided through flow visualization in the header.